RANCANG BANGUN ALAT PEMISAH SAMPAH PADA PERUSAHAAN INDUSTRI - Mochammad Fatkul Ihza; Izza Anshory; Shazana Dhiya Ayuni (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
Population growth in Sidoarjo Regency accompanied by increasing industrial waste has a negative impact on environmental sustainability and provides challenges related to innovation regarding this problem. Waste separator equipment in industrial companies is one of the relevant innovations to make it easier to process the waste produced. This research aims to create a waste separation device based on Internet of Things (IoT) technology that can help people sort waste automatically. This system uses a combination of STM32F407 and ESP8266 microcontrollers with three main sensors: inductive proximity, capacitive proximity, and infrared. This tool is designed to help identify types of metal, non-metal, organic and inorganic waste by automatically moving the waste to the appropriate container with the help of a servo motor. Notifications in the form of trash bin capacity status are also sent via the Telegram application on smartphones. Test results show that this tool is successful in sorting waste with a high level of accuracy, although notification speed depends on the stability of the internet connection. This research provides innovative solutions to waste management challenges and is expected to encourage the application of the 3R principles (reuse, reduce, recycle) in society.Keywords: IoT, Waste Sorting, Sensors, Automation, Waste Management